Construction of a cationic organic network for highly efficient removal of anionic contaminants from water. (4th July 2019) - Li, Zhi-Jun; Xue, Hua-Dong; Zhang, Yu-Quan; Hu, Huai-Sheng; Zheng, Xu-Dong
Abstract : A new cationic organic network is constructed by a facile method from commercially available precursors, and exhibits high efficiency for removal of water contaminants. Abstract : Widespread water contamination has become a great threat to human survival, and therefore developing an efficient strategy for decontamination of wastewater is of great significance. Herein, a new cationic organic network (CON-1 ) has been constructed by a facile method from commercially available precursors, 1, 4-bis(bromomethyl)benzene (BBMB) and 5, 10, 15, 20-tetra(4-pyridyl)porphyrin (TPP), via a quaternization reaction. After being well characterized, CON-1 was employed as an adsorbent for removal of anionic contaminants in aqueous media. Benifitting from the charged framework and exchangeable counter ions, CON-1 exhibits fast adsorption kinetics and high adsorption capacity towards organic dyes and dichromate. The maximum adsorption capacity for the organic dye orange G and Cr2 O7 2− can reach up to 718 mg g −1 and 293 mg g −1, respectively. Moreover, CON-1 displays good stability in the adsorption process, it can be regenerated and it can be reused for several cycles. The facile synthesis, high efficiency, and good stability endowCON-1 with great potential in the purification of wastewater.